Transperineal Ultrasound as an Adjunctive Modality in the Evaluation of ‘H or N’ Type of Recto-urethral Fistula: Technical Note - Bharathi Ravisandhiran; Stuti Chandola; Deeksha Bhalla; Minu Bajpai; Devasenathipathy Kandasamy; Manisha Jana (Indian Journal of Radiology and Imaging, 2023)
Anorectal malformations (ARMs) encompass a complex spectrum of congenital anomalies and H/N type anorectal malformations are extremely rare. In the presence of colostomy, an augmented pressure colostogram with or without retrograde or micturating cystourethrogram is the investigation of choice. Transperineal ultrasound is an imaging technique that allows a fairly accurate morphological assessment of ARMs along with dynamic evaluation of the anorectal structures and pelvic floor anatomy. Here we describe the role of transperineal ultrasound as an adjunctive modality in diagnosis of one such complex anomaly.